Comprehensive molecular screening strategy of OCLN in band‐like calcification with simplified gyration and polymicrogyria. Issue 2 (3rd August 2017) - Jenkinson, E.M.; Livingston, J.H.; O'Driscoll, M.C.; Desguerre, I.; Nabbout, R.; Boddaert, N.; Soares, G.; Gonçalves da Rocha, M.; D'Arrigo, S.; Rice, G.I.; Crow, Y.J.
Abstract : Occludin ( OCLN ) is an important component of the tight junction complex, providing apical intercellular connections between adjacent cells in endothelial and epithelial tissue. In 2010 O'Driscoll et al reported mutations in OCLN to cause band‐like calcification with simplified gyration and polymicrogyria (BLC‐PMG). BLC‐PMG is a rare autosomal recessive syndrome, characterized by early onset seizures, progressive microcephaly, severe developmental delay and deep cortical gray matter and basal ganglia calcification with symmetrical, predominantly fronto‐parietal, polymicrogyria. Here we report 4 additional cases of BLC‐PMG with novel OCLN mutations, and provide a summary of the published mutational spectrum. More generally, we describe a comprehensive molecular screening strategy taking into account the technical challenges associated with the genetic architecture of OCLN, which include the presence of a pseudo‐gene and copy number variants. Abstract :